The professional reality of “Compliance” and some aspects of their legal relationship: Spanish and Italian Law - Velasco-Perdigones, Juan Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The legal person’s liability (criminal or administrative) is a European phenomenon that transfers relevance to different disciplines. Implementing a corporate ethics and compliance culture in Italy and, subsequently, in Spain has led to a revolution in the punitive and sanctioning sphere and the strictly legal-private globe. This paper aims to carry out a comparative study (between Italy and Spain) of the regulation of the phenomenon of Compliance to subsequently offer some notes on the legal relationship between “Compliance” and the civil liability of the compliance officer (OdV).
Keywords: compliance; supervision; compliance officer; professional relationship; contract; liability; damage